Effect of Probiotic â€œL.Reuteriâ€ Association on the Reduction of Serum Bilirubin in Neonatal Jaundice - Makhoul, G.; Mardini, J.; Ojaimi, M. Al; AbiFares, G.; Hanna, P.; Alameddine, A.; Feghali, H.; Makhoul, P.; Saaybi, J.; Nicolas, G.; Sakka, J.; Khalife, M. C. Fadous (European Scientific Journal, ESJ, 2018)
Objective: Evaluate the effect of probiotics association in reducing the total bilirubin level in the serum of neonates with jaundice. Methods: 69 neonates with indirect hyperbilirubinemia were divided randomly into two groups: control and treatment. The control group was treated using phototherapy and the treatment group was treated using phototherapy plus L.Reuteri probiotic. Inclusion criteria: all term newborns admitted for phototherapy for unconjugated hyperbilirubinemia. Exclusion criteria: septic or ill newborn, phenobarbital therapy, transfusion and parents â€˜refusal to enter the study. Baseline bilirubin level was obtained prior to initiating phototherapy and then daily for an average of 3 days. Results: Before treatment, the level of bilirubin was similar in the two groups (p>0.05). We noted a more significant difference in bilirubin at day 1 (p=0.000), day 2 (=0.000) and day 3 (p=0.000) during treatment in the probiotic group when compared to the control group. We also noticed a more significant decrease in bilirubin between day 1 and day 2 (p=0.000) and between day 2 and day 3 (p=0.000) in the probiotic group when compared to the control group. Conclusion: The decrease of bilirubin in neonates with jaundice is more rapid and more significant in the group receiving probiotics as an adjuvant to phototherapy in case of presence of incompatibility or not.